Gestão de resíduos da construção civil: o que tem sido feito no município de São Paulo? - Pinto, Pedro Maciel de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This paper discusses the recent history of public sanitation in the country until the adoption of specific laws and norms in the treatment of solid waste so that Brazil can follow world trends in their management. With the purpose of contributing to the dissemination of the advantages of the use of recycled material, the present work aimed to establish, through the use of the online database of the National Sanitation Information System, a comparative information of public and private behavior in the generation, disposal, collection and reuse of solid waste, with a focus on solid waste construction. Were demonstrated highlighted cases in some of the major cities of the country, both positives and negatives, realizing a comparative analyse and a detailed study at São Paulo. In parallel with this analysis, the role of the Civil Engineer in the awareness of society, especially the professional community, was presented in relation to the benefits of good management of the use and reuse of construction waste. The methodology of work was done through field research, analysis of Laws, Norms and government programs correlating databases like the SNIS. It was possible to obtain data related to regional behaviors in Brazil and to compare the aspects verified in countries with very evolved waste management systems. The results showed that Brazil still presents public policies in development and still very recent ones. With due proportions and high levels of social inequality, it was possible to verify the positive interest of public agencies through budgetary incentives to municipalities that comply with the requirements of Laws

Este trabalho discorreu sobre o histórico recente do saneamento público no país até a adoção de leis e normas específicas no tratamento dos resíduos sólidos para que o Brasil possa acompanhar as tendências mundiais na gestão dos mesmos. Com o intuito de contribuir para a disseminação das vantagens do uso de material reciclado, o presente trabalho visou estabelecer, através do uso da base de dados online do Sistema Nacional de Informação sobre Saneamento, um comparativo de informações do comportamento público e privado na geração, descarte, coleta e reuso dos resíduos sólidos, com foco para os resíduos sólidos da construção civil. Foram demonstrados casos em destaque em algumas das maiores cidades do país, tanto positivos quanto negativos, realizando uma análise comparativa e um estudo detalhado com o município de São Paulo. Em paralelo à essa análise, foi apresentado o papel do Engenheiro Civil na conscientização da sociedade, em especial da comunidade profissional, com relação aos benefícios de uma boa gestão de uso e reuso dos resíduos da construção civil. A metodologia de trabalho se deu através de pesquisas de campo, análises de Leis, Normas e programas governamentais correlacionando a bases de dados como o SNIS. Foi possível obter dados relacionados aos comportamentos regionais no Brasil e comparar aos aspectos verificados em países com sistemas de gerenciamento de resíduos bastante evoluídos. Os resultados mostraram que o Brasil ainda apresenta políticas públicas em desenvolvimento e ainda muito recentes. Guardadas as devidas proporções e os altos índices de desigualdade sociais, foi possível verificar o interesse positivo por parte de órgãos públicos através de incentivos orçamentários aos municípios que cumprirem com requisitos previstos em Leis
Management of construction waste: what has been done in the municipality of São Paulo?
Keywords: Resíduos sólidos; Construção civil; Políticas públicas; Reaproveitamento (Sobras, refugos, etc.); Building